2021
DOI: 10.1186/s12888-021-03207-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and physical abuse and depressive symptoms in the UK Biobank

Abstract: Background The association between sexual and physical abuse and subsequent depression is well-established, but the associations with specific depressive symptoms and sex differences remain relatively understudied. We investigated the associations of sexual and physical abuse with depressive symptoms in men and women in a large population cohort. Methods Observational study based on 151,396 UK Biobank participants. Exposures included self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The etiology of depression is complex; environment, genetics, and epigenetics may all play important roles [ 39 ]. Other risk factors include physical or sexual abuse, low self-esteem, anxiety disorder, borderline personality disorder, post-traumatic stress disorder, chronic diseases such as diabetes, multiple sclerosis, or cancer, alcohol, or drug use, certain prescription medications, family history of depression, and age, gender, race, and geography [ 40 42 ]. There is now accumulating evidence from both high-income countries (HIC) and LMIC that older women, women with no or low education, women from poorer households reporting food insecurity, and women experiencing co-morbidities more often experience depression during their pregnancy [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of depression is complex; environment, genetics, and epigenetics may all play important roles [ 39 ]. Other risk factors include physical or sexual abuse, low self-esteem, anxiety disorder, borderline personality disorder, post-traumatic stress disorder, chronic diseases such as diabetes, multiple sclerosis, or cancer, alcohol, or drug use, certain prescription medications, family history of depression, and age, gender, race, and geography [ 40 42 ]. There is now accumulating evidence from both high-income countries (HIC) and LMIC that older women, women with no or low education, women from poorer households reporting food insecurity, and women experiencing co-morbidities more often experience depression during their pregnancy [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the HPA axis is activated, glucocorticoids are produced by the adrenal cortex ( Li et al, 2016 ) . HPA axis dysregulation, leading to high cortisol reactivity, has been regarded as contributing to the somatic symptoms of depression ( Chaplin et al, 2021 ).…”
Section: Pathophysiological Mechanisms Of Psdmentioning
confidence: 99%
“…While the mechanism by which ACEs may lead to increased dysregulation of biomarkers is not well understood, research focused on physical and sexual abuse in women demonstrate an increased risk of mental illness and depressive symptoms, 46 48 which may impact health behaviors and physical well-being in adulthood, thereby mediating the observed associations. For example, Barboza Solís et al 1 reported a significant association between childhood adversity and AL in adult women, but after controlling for health behaviors at the age of 23 the association disappeared, indicating strong mediation by health behavior.…”
Section: Discussionmentioning
confidence: 99%